ANALYSIS OF GROUP INVESTIGATION LEARNING MODEL ON INCREASING LEARNING OUTCOMES - Selviana Tamo Ina; Desak Made Anggraeni; Oktavianus Deke (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2023)
This study aims to analyze the group investigative learning model on improving learning outcomes. The use of learning models is one of the complex things that can help students to support the learning process well. In this case, the learning model used must be in accordance with the environment and circumstances of students at school. One of the efforts or methods used to overcome when using the group investigation learning model. This study aims to analyze the group investigation learning model on improving student learning outcomes. The results of data analysis show that the group investigation learning model can improve student learning outcomes. This type of research is a literature study by analyzing articles with books that are relevant to the problem being studied. All article-journals state that it can activate students' learning processes and can improve students' cognitive learning outcomes. The results of the study from the book illustrate that the use of the group investigation learning model can involve students by finding out for themselves the information and problems that will be studied. Based on the results of the study, it can be concluded that the group investigation learning model can improve student learning outcomes.